Normativity in Environmental Reporting: A Comparison of Three Regimes - Chelli, Mohamed (Journal of business ethics, 2018)
Normativity is assessed as we evaluate and compare the environmental reporting practices of a sample of French and Canadian companies through the lens of institutional legitimacy. More specifically, we examine how French and Canadian firms changed their reporting practices in reaction to the promulgation of laws and regulations in their respective countries, i.e., the NER and Grenelle II Acts in France, and National Instrument 51-102 and CSA Staff Notice NR 51-333, issued by the Canadian Securities Administrators. The firms’ voluntary disclosures according to GRI guidelines are also investigated. Substantive legitimacy theory is used to explore the level of substantive disclosures provided by Canadian and French firms. The findings reveal that the French parliamentary regime is more successful than the Canadian stock exchange regulation in triggering environmental reporting, and that the GRI combined with local regimes prompts environmental disclosures. Notwithstanding the improvements in environmental reporting under all three regimes, a very low level of substantive disclosure is noted in both countries.